Challenges in mechanics of time dependent materials. Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2016 Annual Conference on Experimental and Applied Mechanics. Volume 2 : ([2017]) - Unknown
No abstract available